Distribution of Endemic Diseases Using Correspondence Analysis: Case Study of Endemic Diseases in Bali Province - Asa Vira Safitri; I Komang Gde Sukarsa; Eka N Kencana (Dinasti Publisher, 2024)
One of the health problems faced by the Indonesian people and related stakeholders is the potential for extraordinary events (KLB) caused by the spread of endemic diseases, including pulmonary tuberculosis, diarrhea, dengue hemorrhagic fever, and malaria. As infectious diseases, these four diseases are classified as endemic considering that their potential for emergence is closely related to the topography of an area. This research aims to elaborate and study the relationship between pulmonary tuberculosis, diarrhea, dengue fever, and malaria with the topography of 57 sub-districts in Bali Province using correspondence analysis. Using secondary data from 9 city district health offices in Bali regarding the number of each disease in 2022. The topography of the 57 sub-districts in Bali Province is classified into 4 altitude groups, namely lowland, low-medium plains, medium-high plains, and low-high plains. The contingency table as the main data for analysis is a matrix of size 4 × 4. The results of the analysis show that pulmonary tuberculosis tends to be observed in the low-high plains, diarrhea tends to occur in low-medium plains and medium-high plains, while dengue hemorrhagic fever and malaria tend to be observed in the lowlands.